Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

Nasal inhalation of antiviral microparticulate powders to target early infection of upper airways - Sabrina Banella; Eride Quarta; Martina Brandolini; Laura Grumiro; Vittorio Sambri; Giovanna Trevisi; Ruggero Bettini; Paolo Colombo; Francesca Buttini; Fabio Sonvico; Georgeta Caraua; Alessandra Rossi; et al. (Drug Delivery and Translational Research, 2026)

Reducing effects of isoliquiritigenin, a naturally occurring GABAB receptor agonist, on alcohol-motivated behaviors in alcohol-preferring rats - Paola Maccioni; Laura Regonini Somenzi; Mauro A. M. Carai; Federico Corelli; Gian Luigi Gessa; Giancarlo Colombo (Psychopharmacology, 2026)
Rationale and objectives Glycyrrhiza glabra L. (Fabaceae; licorice) is a widely used medicinal herb known to exert protective effects against multiple neurological diseases. The flavonoid, isoliquiritigenin (ISL), is a main constituent of roots of Glycyrrhiza glabra . ISL has been reported to behave as a GABA B receptor agonist and exert multiple pharmacological effects. Given the role of the GABA B receptor in the neurobiological and pharmacological bases of alcohol use disorder, the present study investigated the effect of ISL on a series of alcohol-related behaviors in selectively bred, female Sardinian alcohol-preferring rats. Methods and results The collected results indicated that acute treatment with ISL (5-20 mg/kg, i.p.; 50-200 mg/kg, i.g.) decreased operant oral alcohol self-administration under both fixed and progressive ratio schedules of reinforcement and suppressed cue-induced reinstatement of alcohol seeking. ISL effect on alcohol self-administration was partially blocked by pretreatment with the GABA B receptor antagonist, SCH50911, and potentiated by co-administration of the positive allosteric modulator of the GABA B receptor, GS39783. Acute treatment with doses of ISL as high as 80 mg/kg (i.p.) did not alter spontaneous locomotor activity, suggestive of the specificity of ISL effects on alcohol-related behaviors. Conclusions These results confirm the ability of ISL to behave in vivo as a GABA B receptor agonist; they also indicate that ISL reproduced the suppressing effects of the prototypic GABA B receptor agonist, baclofen, on multiple alcohol-related behaviors in rodents.

The italian national genomic strategy: current status, challenges, and future perspectives in clinical practice and public health - Francesco Andrea Causio; Sara Farina; Alessandra Maio; Flavia Beccia; Luigi Russo; Valentina Baccolini; Matteo Chiara; Americo Cicchetti; Gualtiero I. Colombo; Giovanni Comandé; Domenico Coviello; Ruggero De Maria; et al. (Journal of Community Genetics, 2025)
This article presents the outcomes of a national initiative aimed at developing a technical document to support the future Italian National Genomic Strategy, carried out from 2021 to 2024 through the collaboration of 14 research institutions. The project was designed to align with major European genomic initiatives, particularly the “1 + Million Genomes” (1 + MG) Declaration and its supporting programs, including Beyond 1 Million Genomes (B1 + MG), the Genomic Data Infrastructure (GDI), and Genome of Europe (GoE). The initiative was structured around 12 National Mirror Groups (NMGs), each addressing a specific domain such as clinical implementation, ethical and legal issues, data governance, health economics, and public engagement. Through expert consensus and coordinated activities, the project produced a comprehensive technical document outlining seven strategic lines and related intervention areas. These include the integration of genomic testing into clinical practice, development of specialized genomic centers, creation of a national genomic data infrastructure, professional training, and public education. The proposed strategy emphasizes equitable access to genomic medicine, the use of health technology assessment to evaluate new technologies, and the importance of citizen engagement and literacy. By fostering collaboration among institutions, healthcare professionals, and the public, the final goal is to position Italy as a leader in genomic medicine and ensure the responsible, effective, and ethical use of genomics in public health and clinical care.

Aspartic proteases from Silybum marianum: different plant-specific inserts, different destinations - M. Laura Colombo; Agustina Fernández; Constanza S. Liggieri; Pablo Tornero; Laura S. Bakás; Sandra E. Vairo-Cavalli (Planta, 2025)

Sustainability in urban agriculture: The role of biochar in enhancing the productive capacity of compost-based growing media for rooftop farming - Giuseppe Picca; Asier Goñi-Urtiaga; Laura Lozano de Sosa; Maria Victoria Colombo Rodriguez; Isabel Fernández Navarro; César Plaza; Marco Panettieri (Urban Forestry & Urban Greening, 2025)

Residues of agrochemicals in beebread as an indicator of landscape management - Gherardo Bogo; Valeria Caringi; Sergio Albertazzi; Vittorio Capano; Roberto Colombo; Amanda Dettori; Irene Guerra; Giulia Lora; Laura Bortolotti; Piotr Medrzycki (Science of The Total Environment, 2024)

Thermal effects and biological response of breast and pancreatic cancer cells undergoing gold nanorod-assisted photothermal therapy - Leonardo Bianchi; Sara Baroni; Gabriela Paroni; Martina Bruna Violatto; Giulia Yuri Moscatiello; Nicolò Panini; Luca Russo; Fabio Fiordaliso; Laura Colombo; Luisa Diomede; Paola Saccomandi; Paolo Bigini (Journal of Photochemistry and Photobiology B: Biology, 2024)

The impact of behavioural weight management interventions on eating behaviour traits in adults with overweight or obesity: a systematic review and meta-analysis - Laura Kudlek; Patricia Eustacio Colombo; Amy Ahern; Struan Tait; Natasha Reid; Milindu Wickramarachchi; Aiswarya Lakshmi; Stephen J. Sharp; Marie Spreckley; Julia Mueller; Rebecca A. Jones (Appetite, 2024)

The impact of behavioural weight management interventions on eating behaviour traits in children with overweight or obesity: systematic review and meta-analysis - Patricia Eustachio Colombo; Milindu Wickramarachchi; Aiswarya Lakshmi; Laura Kudlek; Amy Ahern; Struan Tait; Natasha Reid; Rebecca A. Jones; Andrea D. Smith (Appetite, 2024)

Exposure to secondhand and thirdhand smoke in private vehicles: Measurements in air and dust samples - Xavier Continente; Elisabet Henderson; Laura López-González; Esteve Fernández; Olena Tigova; Sean Semple; Rachel O'Donnell; Ana Navas-Acién; Núria Cortés-Francisco; Noelia Ramírez; Ruaraidh Dobson; Maria José López; et al. (Environmental Research, 2023)

Towards achieving circularity and sustainability in feeds for farmed blue foods - Stefanie M. Colombo; Koushik Roy; Jan Mraz; Alex H. L. Wan; Simon J. Davies; Sean M. Tibbetts; Margareth Øverland; David S. Francis; Melissa M. Rocker; Laura Gasco; Emma Spencer; Marc Metian; et al. (Reviews in Aquaculture, 2023)
The aims of this review are to describe the role of ‘blue‐food production’ (animals, plants and algae harvested from freshwater and marine environments) within a circular bioeconomy, discuss how such a framework can help the sustainability and resilience of aquaculture and to summarise key examples of novel nutrient sources that are emerging in the field of fed‐aquaculture species. Aquaculture now provides >50% of the global seafood supply, a share that is expected to increase to at least 60% within the next decade. Aquaculture is an important tool for reducing resource consumption in global protein production and increasing resilience to climate change and other global disruptions (i.e. pandemics, geo‐political instability). Importantly, blue foods also provide essential nutrition for a growing human population. Blue foods are helping to help the global goal of ‘zero hunger’ (United Nation's Sustainable Development Goal 2) while reducing the dependency on finite natural resources but further refinement and new solutions are needed to make the industry more ‘circular’ and sustainable, particularly with respect to sourcing raw materials for aquafeeds. This review describes the feed resources that are available or may be created within a circular bioeconomy framework, their role within the framework and in aquaculture and ultimately, how these resources contribute to de‐risking and establishing a resilient aquaculture production chain.

Database development and survival analysis in a clinical and historical cohort of dogs affected by myxomatous mitral valve disease treated or not with pimobendan using causal inference techniques - Mara Bagardi; Valentina Palermo; Chiara Locatelli; Fabio Maria Colombo; Laura Pazzagli; Paola G. Brambilla (Veterinary Research Communications, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

2D and 3D numerical models to evaluate trabecular bone damage - Federica Buccino; Chiara Colombo; Daniel Hernando Lozano Duarte; Luca Rinaudo; Fabio Massimo Ulivieri; Laura Maria Vergani (Medical & Biological Engineering & Computing, 2021)
The comprehension of trabecular bone damage processes could be a crucial hint for understanding how bone damage starts and propagates. Currently, different approaches to bone damage identification could be followed. Clinical approaches start from dual X-ray absorptiometry (DXA) technique that can evaluate bone mineral density (BMD), an indirect indicator of fracture risk. DXA is, in fact, a two-dimensional technology, and BMD alone is not able to predict the effective risk of fractures. First attempts in overcoming this issue have been performed with finite element (FE) methods, combined with the use of three-dimensional high-resolution micro-computed tomographic images. The purpose of this work is to evaluate damage initiation and propagation in trabecular vertebral porcine samples using 2D linear-elastic FE models from DXA images and 3D linear FE models from micro-CT images. Results show that computed values of strains with 2D and 3D approaches (e.g., the minimum principal strain) are of the same order of magnitude. 2D DXA-based models still remain a powerful tool for a preliminary screening of trabecular regions that are prone to fracture, while from 3D micro-CT-based models, it is possible to reach details that permit the localization of the most strained trabecula. Graphical abstract

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Correction to: Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Short-Term Effects of Genetically Modified Potato on Arbuscular Mycorrhizal Fungal Communities - Betina I. Stephan; Roxana P. Colombo; Vanesa A. Silvani; Mariana Pérgola; Alicia M. Godeas; Alejandro G. Pardo; Laura Fernández Bidondo (Journal of Soil Science and Plant Nutrition, 2019)

The calcium-binding type III repeats domain of thrombospondin-2 binds to fibroblast growth factor 2 (FGF2) - Marco Rusnati; Patrizia Borsotti; Elisabetta Moroni; Chiara Foglieni; Paola Chiodelli; Laura Carminati; Denise Pinessi; Douglas S. Annis; Giulia Paiardi; Antonella Bugatti; Alessandro Gori; Renato Longhi; et al. (Angiogenesis, 2019)

Expression of the Parkinson’s Disease-Associated Gene Alpha-Synuclein is Regulated by the Neuronal Cell Fate Determinant TRIM32 - Maria Angeliki S. Pavlou; Nicoló Colombo; Sandra Fuertes-Alvarez; Sarah Nicklas; Laura Gonzalez Cano; Maria C. Marín; Jorge Goncalves; Jens C. Schwamborn (Molecular Neurobiology, 2017)

Arbuscular mycorrhizal fungal diversity in high-altitude hypersaline Andean wetlands studied by 454-sequencing and morphological approaches - Vanesa Analía Silvani; Roxana Paula Colombo; María Victoria Scorza; Laura Fernández Bidondo; Carolina Paola Rothen; Adalgisa Scotti; Sebastián Fracchia; Alicia Godeas (Symbiosis, 2017)

Validation of FreeSurfer-Estimated Brain Cortical Thickness: Comparison with Histologic Measurements - Francesco Cardinale; Giuseppa Chinnici; Manuela Bramerio; Roberto Mai; Ivana Sartori; Massimo Cossu; Giorgio Lo Russo; Laura Castana; Nadia Colombo; Chiara Caborni; Elena De Momi; Giancarlo Ferrigno (Neuroinformatics, 2014)

ST1859 reduces prion infectivity and increase survival in experimental scrapie - Laura Colombo; Paola Piovesan; Orlando Ghirardi; Mario Salmona; Gianluigi Forloni (Archives of Virology, 2009)

Therapeutic Paint of Cidofovir/Sucralfate Gel Combination Topically Administered by Spraying for Treatment of orf virus Infections - Fabio Sonvico; Gaia Colombo; Laura Gallina; Fabrizio Bortolotti; Alessandra Rossi; Colin J. McInnes; Gina Massimo; Paolo Colombo; Alessandra Scagliarini (The AAPS Journal, 2009)

Different properties of P2X7 receptor in hippocampal and cortical astrocytes - Fabio Bianco; Alessio Colombo; Laura Saglietti; Davide Lecca; Maria Pia Abbracchio; Michela Matteoli; Claudia Verderio (Purinergic Signalling, 2009)

Development of Genus/Species-Specific PCR Analysis for Identification of Carnobacterium Strains - Mauro Scarpellini; Diego Mora; Silvia Colombo; Laura Franzetti (Current Microbiology, 2002)